Tolerability of ivermectin in gnathostomiasis - Valai Bussaratid (2018)
At present, no universally-accepted effective treatment for cutaneous gnathostomiasis is available. At the Hospital for Tropical Diseases, Mahidol University, albendazole 400 mg twice a day for 14 days is commonly prescribed for patients diagnosed with cutaneous gnathostomiasis. The efficacy of albendazole to induce outward migration of the parasite was less than or around 20% in 2 studies. Research for alternative, more efficacious treatment, is needed. In this prospective open-labeled study, we assessed the safety of ivermectin in 20 Thai patients diagnosed with cutaneous gnathostomiasis. Ivermectin, one time only, at dosages of 50, 100, 150, or 200 μg/kg bodyweight, was given orally to 4 groups of patients, 5 patients each group. Adverse events were recorded and laboratory tests were obtained before and after treatment. No serious adverse events occurred in this study. Forty adverse events were possibly related to ivermectin. The adverse events were malaise (35%), myalgia (30%), drowsiness (30%), pruritus (20%), nausea/vomiting (20%), dizziness (15%), diarrhea (15%), feeling of shortness of breath (10%), feeling of palpitations (10%), constipation (5%), anorexia (5%), and headache (5%). These adverse events were self-limited and not dose-related. Laboratory abnormalities were found in 3 patients (15%). Transient microscopic hematuria, pyuria, and mildly elevated liver enzymes were found in 1 patient each. Ivermectin single dose, of 50, 100, 150, and 200 μg/kg bodyweight, is considered safe in Thai patients. Future trials of ivermectin on human gnathostomiasis may be performed using dosages up to 200 μg/kg bodyweight.